Vietnamese lecturers’ perceptions of using the flipped classroom model in enhancing EFL students’ speaking skills - Giang, Nguyen Truong (American Journal of Education and Learning, 2026)
The purpose of this study is to examine the views of Vietnamese university lecturers regarding applying the Flipped Classroom (FC) to improve their students' speaking skills in English as a Foreign Language (EFL). A qualitative, interpretive methodology was used for this study; semi-structured interviews, two focus groups, and two pedagogical workshops were conducted with 25 English-major lecturers from five different universities located in Ho Chi Minh City. Data collected in the course of this study were analyzed using thematic analysis via a six-phase process. Overall, findings indicated strong support among participants for the use of the FC model and general agreement that the model had the potential to increase learners' engagement, confidence, and English-speaking skills, including oral fluency. While there were several challenges noted by participants regarding the implementation of the FC model, such as a lack of adequate technological infrastructure and the low level of digital literacy among learners and teachers, participants reported making a number of context-based adaptations to facilitate learner participation and inclusiveness. These adaptations included modifying materials to be mobile-friendly, developing culturally responsive speaking tasks, and partially flipping their courses. The results include practical suggestions for adapting globally developed pedagogical models to the sociocultural and institutional realities of Vietnam, thereby providing a foundation for sustainable and communicative reform in higher education.